2012
DOI: 10.1097/mao.0b013e31826a50c3
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Catheter Dilatation of Eustachian Tube

Abstract: Endoscopic transnasal ET balloon dilation is a novel approach to treating ET dysfunction. Benefits can be durable up to 3 years. This technique holds much promise and merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 13 publications
3
113
0
1
Order By: Relevance
“…Nine prospective studies, 4,6,[8][9][10][11][12][13][14] describing 713 eustachian tube balloon dilations in 474 patients (aged 18-86 years), were identified. Follow-up duration ranged from 1.5 to 18 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine prospective studies, 4,6,[8][9][10][11][12][13][14] describing 713 eustachian tube balloon dilations in 474 patients (aged 18-86 years), were identified. Follow-up duration ranged from 1.5 to 18 months.…”
Section: Resultsmentioning
confidence: 99%
“…More serious complications included two cases of self-resolving subcutaneous emphysema in two separate studies. 4,13 Complications associated with a learning curve were described by Wanscher and Svane-Knudsen, 14 who reported 3 cases of acute otitis media in the first 20 eustachian tube balloon dilations, which decreased to 1 out of 30 after 5 days of post-operative prophylactic oral antibiotics.…”
Section: Complicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…В данном случае основным оценочным критерием являлось состояние барабан-ной перепонки [21]. В других исследованиях основ-ное внимание уделялось не тимпанометрическим данным, а пробе Вальсальвы, а также субъективной оценке состояния пациентов [22][23][24][25]. C нашей точки зрения, не менее важно определить, насколько бы-стро наступают или не наступают изменения в венти-ляции полости среднего уха.…”
Section: Discussionunclassified
“…Due to risk of injury to the ICA, balloon dilation of the bony ET is contraindicated. 55 Jurkiewicz et al, 56 McCoul et al, 19 Tisch et al, 57 Catalano et al, 58 Schröder et al, 59 Silvola et al, 60 again Schröder et al, 21 and Dalchow et al 61 reported successful outcomes of balloon dilation. Kivekäs et al 62 compared biopsies of the ET mucosa before and after balloon dilation and found reduction of inflammatory epithelial changes and submucosal inflammatory infiltrate after the balloon procedure.…”
Section: Treatmentmentioning
confidence: 99%